The potential impact of experiencing social inclusion in recreation for children with and without disabilities. Issue 14 (3rd July 2022) - Edwards, Brydne; Cameron, Debra; King, Gillian; McPherson, Amy C.
Abstract: Purpose: Inclusive recreation programs can have individual and community impacts for children with and without disabilities. However, studies that explore the impact of such programs on children's attitudes are mixed. The purpose of this study was to explore the perspectives of children with and without disabilities on the individual impact of an inclusive recreation program. Material and Method: This study adopted a generic qualitative methodology. Interviews were conducted with participants between the ages of eight and 18 enrolled in the same program and each participant was interviewed twice. Inductive thematic analysis was used to analyze results. Results: 17 participants were recruited for this study, which included nine children without disabilities (CWODs) and eight children with disabilities (CWDs). This study revealed five themes: a) CWODs have limited exposure to people with disabilities; b) CWODs and CWDs' hopes of change; c) CWODs learned how to interact with people with disabilities; d) CWODs reported greater perceived similarity in functional ability and hobbies/interests between themselves and CWDs, and; e) CWODs become more comfortable being around people with disabilities. Conclusions: This study helps broaden understandings of how inclusive experiences in recreation settings impact children with and without disability. IMPLICATIONS FOR REHABILITATION: Children without disabilities can develop more positive attitudes toward children with disabilities in affective and cognitive domains after participating in an inclusive recreation program. Incorporating inclusive language into program design and implementation may promote positive attitudes toward diversity in recreation settings. Children without disabilities would benefit from more opportunities to interact with children with disabilities in unstructured, inclusive or integrated recreation settings.